2009
DOI: 10.1002/jssc.200800708
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of stir bar sorptive extraction of polar phenols in water followed by HPLC separation in poly(vinylpyrrolididone‐divinylbenzene) monolith

Abstract: Development and validation of stir bar sorptive extraction of polar phenols in water followed by HPLC separation in poly(vinylpyrrolididonedivinylbenzene) monolith An effective and simple method for polar phenols in water matrix was developed by using stir bar sorptive extraction (SBSE) based on a hydrophilic poly(vinylpyrrolididone-divinylbenzene) (VPDB) monolithic material and HPLC analysis. To achieve optimum extraction performance for phenols, several parameters, including extraction and desorption time, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 39 publications
(31 reference statements)
2
23
0
Order By: Relevance
“…It has been found that phenol produces many adverse effects on fish and aquatic ecosystem when chronically exposed even at a low concentration [2,3]. Therefore, their treatments must be accomplished before the solution can be safely discharged into the nature water resources.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that phenol produces many adverse effects on fish and aquatic ecosystem when chronically exposed even at a low concentration [2,3]. Therefore, their treatments must be accomplished before the solution can be safely discharged into the nature water resources.…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of the current method, it was compared with the other reported methods coupled with HPLC, such as ultrasoundassisted headspace liquid-phase microextraction (UAHS-LPME), 28 solid-phase microextraction with micellar desorption (SPME-MD), 29 stir bar sorptive extraction (SBSE), magnetic solid-phase extraction (MSPE), 31 SPE, 32 ultrasoundassisted HF-LLLME (UA-HF-LLLME), 33 hollow fiberbased supported liquid membrane (HFSLM) 34 and three phase HF-LPME 35 for the determination of CPs from the viewpoint of linear ranges (LRs), LODs, and RSDs. The comparison results are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Huang et al proposed a new monolithic stir-bar for extraction of phenols, avoiding the previous derivatization step [33], simplifying the extraction procedure, and protecting the stir-bar from the negative effects of derivatizing reagents. In a similar way, different monolithic stir-bars have been proposed for extraction of analytes covering a wide range of polarity [34][35][36][37]. Moreover, use of a monolithic stir-bar can simplify the overall extraction procedure, as is reported for extraction of sulfonamides from milk [38].…”
Section: Monolithic Based Coatingsmentioning
confidence: 96%